An intelligent phase transformation system based on lyotropic liquid crystals for sequential biomolecule delivery to enhance bone regeneration. Issue 13 (14th March 2023) - Li, Rui; Zhang, Jiao; Shi, Jingyu; Yue, Jiang; Cui, Yongzhi; Ye, Qingsong; Wu, Gang; Zhang, Zhiping; Guo, Yuanyuan; Fu, Dehao
Abstract : A liquid crystal formulation systems containing deferoxamine and simvastatin was developed successfully to stimulate angiogenesis and improve osteogenesis. Abstract : Endogenous repair of critical bone defects is typically hampered by inadequate vascularization in the early stages and insufficient bone regeneration later on. Therefore, drug delivery systems with the ability to couple angiogenesis and osteogenesis in a spatiotemporal manner are highly desirable for vascularized bone formation. Herein, we devoted to develop a liquid crystal formulation system (LCFS) attaining a controlled temporal release of angiogenic and osteoinductive bioactive molecules that could orchestrate the coupling of angiogenesis and osteogenesis in an optimal way. It has been demonstrated that the release kinetics of biomolecules depend on the hydrophobicity of the loaded molecules, making the delivery profile programmable and controllable. The hydrophilic deferoxamine (DFO) could be released rapidly within 5 days to activate angiogenic signaling, while the lipophilic simvastatin (SIM) showed a slow and sustained release for continuous osteogenic induction. Apart from its good biocompatibility with mesenchymal stem cells derived from rat bone marrow (rBMSCs), the DFO/SIM loaded LCFS could stimulate the formation of a vascular morphology in human umbilical vein endothelial cells (HUVECs) and the osteogenic differentiation of rBMSCs in vitro . The in vivo rat femoral defect models have witnessed the prominent angiogenic and osteogenic effects induced by the sequential presentation of DFO and SIM. This study suggests that the sequential release of DFO and SIM from the LCFS results in enhanced bone formation, offering a facile and viable treatment option for bone defects by mimicking the physiological process of bone regeneration.